A review of Lassa fever cases in Nigeria for the year 2020 - Nyinoh, Iveren Winifred; Utume, Laura Nguoron; Bob-Echikwonye, Ooja (International Journal Of Community Medicine And Public Health, 2021)
Lassa fever (LF) is a zoonotic disease endemic in west Africa and the knowledge of its epidemiology is important in the prevention of infection. In Nigeria, LF occurs majorly in the dry months and individuals in rural communities are mostly infected, however, there have been reports of a shift to urban households. Clinical symptoms vary and may be non-specific thus making diagnosis challenging. In this paper, we reported data routinely collected in 2020 from all individuals diagnosed with LF in Nigeria. Data were obtained from the Nigerian centre for disease control (NCDC) website online. Out of 6791 suspected cases from 30 December 2019 to 3 January 2020 there were 1189 laboratory-confirmed cases and 244 deaths. By comparison to the same period in 2019 where there were 833 cases and 74 deaths, this represents an increase of 42.74% confirmed cases from 2019. Data indicates that there was a minimum of 1 confirmed case of LF in 131 local government areas across 27 of the 36 states. Ondo state Nigeria had the highest number of confirmed cases with 75%, which was followed by Edo (32%) and Ebonyi (7%). By age, the 21-30 year old were mostly affected. Collated data showed the numbers of LF cases are significantly increasing yearly. The results obtained will assist the government in mapping the disease and taking precautionary measures to prevent the spread of LF amongst individuals in Nigeria.